2021
DOI: 10.21203/rs.3.rs-678692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Non-Coding RNA LINC01559 Exerts Oncogenic Role Via Enhancing Autophagy in Lung Adenocarcinoma

Abstract: Background: Long non-coding RNAs (lncRNAs) have been verified to play fatal role in regulating the progression of lung adenocarcinoma (LUAD). Although lncRNAs play important role in regulating the autophagy of tumor cells, the function and molecular mechanism of LINC01559 in regulating lung cancer development remain to be elucidated. Method and materials: In this study, we used bioinformatics to screen out autophagy-related lncRNAs from TCGA-LUAD repository, and the least absolute shrinkage and selection opera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…According to the genome-wide miRNA expression pro le data (average normalized count ≥ 1), in the GSE76903 dataset, among the above 14 miRNAs, only hsa-miR-1343-3p had an average expression level greater than 1. Recent studies have found that LINC01559 promotes lung cancer cell proliferation and migration in vitro by enhancing the autophagy signaling pathway via sponging hsa-miR-1343-3p [29]. However, the role of hsa-miR-1343-3p in HCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…According to the genome-wide miRNA expression pro le data (average normalized count ≥ 1), in the GSE76903 dataset, among the above 14 miRNAs, only hsa-miR-1343-3p had an average expression level greater than 1. Recent studies have found that LINC01559 promotes lung cancer cell proliferation and migration in vitro by enhancing the autophagy signaling pathway via sponging hsa-miR-1343-3p [29]. However, the role of hsa-miR-1343-3p in HCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%